New trends in energy production and utilization - Teresa M. Mata (2017)
Energy has been the engine of nations' development, and this has driven mankind towards growing energy needs, in particular for transportation, agricultural and industrial activities and buildings. Energy for transportation is based on oil derived fuel, whereas energy in buildings consists mainly of electricity, which is produced from fossil fuels, nuclear power and/or from renewable energy sources, such as hydro and solar. Agricultural and industrial activities use a combination of fossil fuels and electric energy. To increase the sustainability of energy production and efficient energy use, it is urgent that better monitoring and control systems are used, and increase the energy production from renewable sources. This drives the energy sector towards the need for Life Cycle Analysis of energy processes to support the selection and implementation of more sustainable energy systems, as well as to develop better and more intelligent electric energy grids, where storage energy systems plays an essential role. These questions will be briefly discussed in this paper, focusing in the current situation, existing problems and potential solutions, and expected developments.